MEMBANGUN RELASI UMAT BERAGAMA PASCA KONFLIK AGAMA DI TANJUNGBALAI - Fitriani Fitriani; Indra Harahap; Titah Utari (UIN Sumatera Utara Medan, 2020)
AbstractIn order to create relations between religious communities on the basis of tolerance, it is very important to intensify dialogue between religious communities. Because dialogue is an appropriate resolution in building peace between religious communities. The research results found in this paper related to the post conflict that occurred in Tanjungbalai City is a bridge in creating harmony by fostering tolerance, caring for others and increasing solidarity among fellow communities in Tanjungbalai. This research is a field research. This research emphasizes the function of theory as a tool to sharpen the sensitivity of researchers in seeing religious conflicts in Tanjungbalai and formulating Johan Galtung's conflict triangle theory (peace keeping, peace making and peace building) as a means of building good relations after conflict. The purpose of this study is to build relationships between religious communities in the Tanjungbalai community by removing the truth claim of a religion, feeling suspicious and trying to be inclusive in religion. With this effort, it is expected that a harmonious relationship between religious communities will be created after the Burning of the Vihara in Tanjungbalai. Keywords: Relationships, Religious People and Post-Conflict